Fazer a Poesia Fazendo: Procedimentos e Tentativas de Olhar e Ver o Cotidiano em Marília Garcia - Vieira, Guilherme Alenício Pires de Souza Medeiros (2021)
This research aimed to approach the work of the poet, editor and translator, Marília Garcia, in order to raise reflections on her themes, procedures and thoughts regarding the work with texts. Dividing into two chapters, the first, from the poems “Le pays n’est pas la carte” (2007), “Blind Light” (2014), “Uma partida com Hilary Kaplan” (2014), “Ordem Alfabética” (2014) e “passagem com érica zíngano” (2016), I highlight the association of times, discourses, ideas, the relationships of affection, the contamination by other discourses, the paths that the poet takes in the writing of her texts. Therefore, I highlight, respectively, the lack of differentiation between “reality” and “fiction”, “I” and “other”, “literary text” and “non-literary text”, in dialogue with the ideas of Josefina Ludmer and Florencia Garramuño, particularly with regard to the concepts of “post-autonomous literatures” and “forms of impertinence”, and with Giorgio Agamben, regarding the concept of “whatever singularity”, having in perspective works of contemporary art with which the poet converses. In the second chapter, from the poem “parque das ruínas” (2018), I make considerations about the procedures used, particularly referring to the relationship between text and image, crossing discussions about the photographic episteme and its relationship with writing, in dialogue with Phillipe Dubois (2012), Natalia Brizuela (2014), Walter Benjamin (2012) and Giorgio Agamben (2014). I highlight the interest in everyday life, in what escapes, which implies the poem's refrain about the impossibility of “seeing”. I end the text by summarizing the debates developed in the research and presenting some implications of reading Marília Garcia's books in my experiences with writing, photography and video, especially the video "vista para feira livre", the experiments with questions taken from the poems by Garcia, photographs of fragmented objects, placing these works in the process of developing the dissertation text, as ways of reproducing and testing the poet's procedures.